Du voyage initiatique à l’enseignement : le programme inter-up « Ville orientale » - Diane Aymard (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Created in 1981, the inter-up program named « Ville orientale » has participated to the renewal of the French architecture through its innovative aspect as well as the rediscovery of the extra-occidental architecture by the western occidental intellectuals. This program, created in the contexte of the decolonization which occurred between years 1950 and 1960 and the opening to the world - more precisely to the Third World – with a sincere curiosity for abroad, questions the new relationship between France and developing countries in the architectural community. This raises several points: How did the protagonists of the program « ville orientale » meet with community from abroad? In what perspective this meeting was held? What contributions, immediates and a posteriori, could have generated the activity of such a program in the French and International architectural field?